Cultural Competence and Global Health: Perspectives for Medical Education – Position paper of the GMA Committee on Cultural Competence and Global Health - Mews, Claudia; Schuster, Sylvie; Vajda, Christian; Lindtner-Rudolph, Heide; Schmidt, Luise E.; Bösner, Stefan; Güzelsoy, Leyla; Kressing, Frank; Hallal, Houda; Peters, Tim; Gestmann, Margarita; Hempel, Linn; et al. (GMS Journal for Medical Education, 2018)
Introduction: Routine medical care in Germany, Austria and Switzerland is being increasingly impacted by the cultural and linguistic diversity of an ever more complex world. Both at home and as part of international student exchanges, medical students are confronted with different ways of thinking and acting in relation to health and disease. Despite an increasing number of courses on cultural competence and global health at German-speaking medical schools, systematic approaches are lacking on how to integrate this topic into medical curricula.Methodological approach: This paper is based on a structured consensus-building process by a multidisciplinary committee composed of faculty and students. In a first step, a qualitative online survey was carried out in order to establish an inventory of definitions and concepts. After the second step, in which a literature search was conducted and definitions of global health and transcultural and intercultural competence were clarified, recommendations were formulated regarding content, teaching and institutional infrastructure. Based on small-group work and large-group discussions, different perspectives and critical issues were compiled using multiple feedback loops that served to ensure quality.Results: An inventory on the national and international level showed that great heterogeneity exists in regard to definitions, teaching strategies, teaching formats and faculty qualification. Definitions and central aspects considered essential to medical education were thus established for the use of the terms “cultural competence” and “global health”. Recommendations are given for implementation, ranging from practical realization to qualification of teaching staff and education research.Outlook: High-quality healthcare as a goal calls for the systematic internationalization of undergraduate medical education. In addition to offering specific courses on cultural competence and global health, synergies would be created through the integration of cultural competence and global health content into the curricula of already existing subject areas. The NKLM (the national competence-based catalogue of learning objectives for undergraduate medical education) would serve as a basis for this.